Gelation of Anisotropic Colloids with Short-Range Attraction - Triet, Dang Minh; Quoc Tuan, Truong; Thien, Tran Van (VNU Journal of Science: Mathematics - Physics; Vol 36 No 1DO - 10.25073/2588-1124/vnumap.4451, 2020)
Colloidal gels are space-spanning networks that form solids at dilute particle volume fractions. The kinetic process of gelation is central to understand the flow of complex fluids. Here, we report a simulation study of colloidal gelation of anisotropic colloids with attractive Lennard-Jones potential. These forces quasi-model the critical Casimir effect far from the critical solvent fluctuations acting on colloidal patches. By tuning the depths of the patch-to-patch particle interactions and the selected colloidal patches, we dynamically arrest the colloids to form gels. We find that thermal density fluctuation is the key factor to activate colloidal cluster space spanning: the balance between clustering and break-up mechanism is important for the gelation process of anisotropic systems. These results open new opportunities for studying the structural modifications of colloidal gels formed by anisotropic particles, and shed light on non-equilibrium behavior of anisotropic colloidal building blocks.